Vitamin and mineral levels in children with autism spectrum disorder - Palaz, Mehmet; Civan, Hasret AyyÄ±ldÄ±z; YÄ±lmaz, Semra (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
The aim of this study was to compare the vitamin and mineral values of the patients followed up in the Child Psychiatry Outpatient Clinic with the diagnosis of autism spectrum disorder to healthy controls in the same age group and to investigate whether vitamin-mineral values were related to autism weight (CARS score).Between September 2017 and September 2018, we worked at Bak?rköy Dr. Sadi Konuk Training and Research Hospital Children and Adolescent Mental Health and Diseases outpatient clinic with autism spectrum disorder patients with childhood autism assessment scale (CARS) was weighted. Age, gender, height, weight, blood Iron, Vitamin B12, Folate and 25 (OH) Vitamin D levels of all patients included in the study were recorded. Mann-Whitney U, Pearson chi-square and Fisher's exact test were used to evaluate the data. In this study, 108 patients with ASD were compared with 115 normal cases. There was no statistically significant decrease in Vitamin B12, Folate, Iron and Vitamin D levels in patients with ASD compared to normal patients. According to CARS score, there was no statistically significant difference in vitamin B12, Folate, Iron and Vitamin D levels in children with mild and severe ASD. In our study, it was concluded that vitamin B12, Folate, Iron and Vitamin D levels in children with ASD were not lower than healthy children, and there was no difference between mild and severe cases according to CARS score.